Hantaviruses in Insectivore Populations in Siberia - L. N. Yashina; S. A. Abramov; T. A. Dupal; V. V. Yakimenko; A. K. Tantsev; B. S. Malyshev; M. Yu. Kartashov (Проблемы особо опасных инфекций, 2018)
Objective of the study was investigation of hantaviruses in a new natural reservoir - insectivores, their diversity and geographic distribution in the Western and Eastern Siberia. Materials and methods. Sorex shrews (71 specimens) were captured in Altai Republic, Altai, and Krasnoyarsk Territories, and Omsk Region. All samples were analyzed for hantavirus RNA using reverse transcription polymerase chain reaction with subsequent sequencing. Results and conclusions. A total of 12 viral RNA isolates from two Sorex species (S. araneus and S. roboratus) were genetically typed. Sequence analysis of the partial L and S segments identified two distinct hantaviruses. Kenkeme (KKMV) virus was detected in a flat-skulled shrew (S. roboratus) in Altai Territory. This virus was previously found in geographically remote sites in the Sakha Republic and China. New foci of Seewis virus circulation among common shrews (S. araneus), were found in the Omsk Region, Altai and Krasnoyarsk Territories. Previously published and new findings suggest that hantaviruses among shrews are widely distributed over the Russian Federation territory. The widespread circulation of SWSV and KKMV throughout Siberia is an important argument for investigation of their role in human infections.